Análisis de la dinámica fotosférica a granescala durante el ciclo solar 24 - Quintero Ortega, Valeria; Campos Rozo, Jose Iván; Vargas Domínguez, Santiago (Scientia et Technica, 2018)
The analysis of the movements of the solar photosphere has been used by several authors to study the dynamics of solar plasma at various spatial and temporal scales. This work, in particular, is focused on the study of vertical movements, in order to perform a statistical analysis of the flow maps to characterize some dynamic aspects of the photospheric plasma along the time evolution of the Sun. To carry out this analysis, we used a set of images obtained by the HMI instrument HMI (Helioseismic and Magnetic Imager) aboard the SDO mission (Solar Dynamics Observatory) to which local correlation tracking algorithms (LCT) were applied. they allow the identification of areas of convergence and divergence of the plasma at certain time intervals during the solar cycle 24, thus covering moments of high and low solar activity. The study gives us the reason for the meridional movements showing that in low latitudes the outgoing emergency flow occupied a higher percentage of area, while in the latitudes near the poles the behavior changes, that is, the incoming flows occupy a greater area.